Building on Progress : Reform and Growth in the Middle East and North Africa. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
Countries in the Middle East and North Africa region have unprecedented opportunities for transforming their economies through accelerated economic growth, but the countries themselves must ensure the necessary conditions. This study, by the Middle Eastern Department, focuses on four areas that are fundamental to growth-enhancing structural changes: improving the region's investment performance, fiscal reform, financial sector reform, and trade liberalization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet